CRYSTAL FORMS OF LOMEFLOXACIN: PREPARATION, CHARACTERIZATION AND DISSOLUTION PROFILE - Vellaichamy Ganesan; Raju Thenge; Naresh Vinjamuri; Srinivasarao Prathipati (Indonesian Journal of Pharmacy, 2013)
The present work was undertaken with the synthesis of crystal forms of Lomefloxacin from solvents of varying polarity (polar, protic solvents). The purpose of the present investigation was to employ crystallization techniques in order to improve the solubility and dissolution studies of Lomefloxacin. The experimental methods involved the preparation of lomefloxacin crystals by crystallization from single solvent technique. Crystals were prepared from solvents like distilled water, ethanol and methanol. Prepared crystals were undergone various studies in terms of crystal yield, melting point, true density, solubility and in vitro drug release study as well as characterized by technique viz: FT-IR, differential scanning calorimetry (DSC) and Powder X-ray Diffractometry(PXRD). Photomicrographs of the crystals shows that the crystals obtained from different solvents existed in different shape. Among all the crystals, LOME-I belongs to Type-1 and LOME–II belongs to Type-2 based on instrumental techniques. Highest crystal yield (88%) and maximum density (1.2021g/mL) was observed with LOME-I. Maximum solubility and dissolution rate was observed in LOME-III followed by LOME-II and LOME-I. However all prepared crystal forms showed higher solubility and dissolution profile when compare with commercial Lomefloxacin. It is concluded that the study has indicated the existence of two polymorphic forms of Lomefloxacin which was having better solubility and in vitro release than that of commercial Lomefloxacin.Key words: Polymorphism, Solubility, Dissolution rate, DSC, FT-IR, PXRD